2014
DOI: 10.1177/0954410014542624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inlet conditions on compressor intermediate duct

Abstract: With further development of the turbofan aero-engine, the compressor intermediate duct can no longer be considered to merely perform the service function of transporting fluid from low-pressure component to high-pressure stage. Especially for the practical compressor intermediate duct with inclined uncambered struts, the high-curvature geometry, great internal pressure gradient, and strong three-dimensional effect make it extremely sensitive to the real inflow conditions, which would not be applicable to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…For the core duct, Gao et al. 31 suggest that at least 57 cells in the spanwise direction are required to model the flow pattern in the S-duct efficiently. The same strategy is used in this paper (69 spanwise cells in this study, refinement has shown changes lesser than defined grid-independent error band).…”
Section: Numerical Solver and Meshingmentioning
confidence: 99%
“…For the core duct, Gao et al. 31 suggest that at least 57 cells in the spanwise direction are required to model the flow pattern in the S-duct efficiently. The same strategy is used in this paper (69 spanwise cells in this study, refinement has shown changes lesser than defined grid-independent error band).…”
Section: Numerical Solver and Meshingmentioning
confidence: 99%
“…Reference [11] showed a reduction in pressure gradient at hub and shroud but a rise in losses for a non-struted ICD. Gao et al [12] studied the same effect on a struted ICD. Results proved a significant dependency of secondary flow structure on swirl angle.…”
Section: Introductionmentioning
confidence: 97%
“…Influence of swirl on ICD flow behaviour has been studied by Ref. [11] and Gao et al [12]. Reference [11] showed a reduction in pressure gradient at hub and shroud but a rise in losses for a non-struted ICD.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 Moreover, it has been demonstrated that inlet entry conditions have an impact on the S-duct aerodynamics. 16 , 17 Often, experimental testing and S-duct CFD optimization are required to assess the operability of the propulsion system for a range of different inlet configurations. 18 20 …”
Section: Introductionmentioning
confidence: 99%